A linguagem como forma de vida: uma leitura wittgensteineana sobre a gramática da doença mental no discurso da reforma psiquiátrica - Pinheiro, Marina Assis (2006)
This research focuses on the uses of the expression mental illness in the discursive practices of the Psychiatric Reform. Although vigorously criticized by several authors within this tradition, such expression is recurrently employed in Reform institutions and, in particular, within the Reform s reference texts themselves. Those texts are mainly characterized by: 1. a quest for de-institutionalization; and 2. an attempt to build an ethics of solidarity in regard to madness. This Thesis analyzed several of such bibliographical references, through a method based on Wittgenstein s (Philosophical Investigations) conception of language. As a result of this analysis, I suggest that the notion of mental illness, as used in Reform´s language game, comes to life through a vocabulary that encompasses an interplay between a discourse of negativity and the dynamic construction of a renewed and inclusive social landscape: a new form of life